CBCT Dose Is Reduced with Angular Tube Current Modulation While Maintaining Image Quality and Reducing Photon Starvation Artifacts - Tero Hyvärinen; Samuel Onnela; Timo Liimatainen; Sampo Ylisiurua; Jyri-Johan Paakki; Jyri Järvinen; Michaela K. Bode; Miro-Pekka Jussila; Veli-Pekka Riekki; Matti Hanni; Mikael Brix (Annals of Biomedical Engineering, 2026)
Purpose This study evaluated whether scout-derived angular tube current modulation (ATCM) in cone beam computed tomography (CBCT) can reduce radiation dose while preserving image quality. ATCM is routine in helical CT but remains absent from clinical CBCT and is largely unexplored in the literature. Methods A projection-based intensity-dependent noise model was developed using polymethyl methacrylate slab measurements at 80–120 kV. Posterior-anterior and lateral scout views were used to derive angle-dependent elliptical attenuation estimates and to derive per-angle current-time product profiles. ATCM was emulated using projection data acquired with a clinical CBCT system and tested using anthropomorphic phantoms and a uniform water phantom. Dose-area product (DAP), effective dose based on Monte Carlo calculations, image noise magnitude, and noise texture were compared between modulated and unmodulated reconstructions. Image quality was subjectively evaluated by five board-certified radiologists using blinded paired preference scoring (60 paired reads; 12 pairs × 5 radiologists). Results ATCM reduced DAP by up to 17% and effective dose by up to 20%, while maintaining image quality and noise texture, with improved reader preference in specific protocols. Modulated reconstructions showed reduced photon starvation artifacts in high-attenuation projection views and improved delineation of thoracic vertebra in selected protocols. Radiologists preferred ATCM in 60% of paired comparisons, most consistently for torso and jaw protocols (80 and 60% of paired comparisons, respectively). Conclusion Scout-derived ATCM for CBCT enables dose reduction while maintaining image quality, with improved reader preference in specific protocols, and reduced artifacts.

Operationalising resilience-based management at scale: A meta-adaptive blueprint from the Great Barrier Reef crown-of-thorns starfish control program - Samuel A. Matthews; Michael Bode; Roger Beeden; Mary C. Bonin; Cameron S. Fletcher; Brigid Kerrigan; Isobel Ryan; Jennifer Wilmes; Alice White; David H. Williamson (Biological Conservation, 2026)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Greenhouse gas dynamics in an urbanized river system: influence of water quality and land use - Long Ho; Ruben Jerves-Cobo; Matti Barthel; Johan Six; Samuel Bode; Pascal Boeckx; Peter Goethals (Environmental Science and Pollution Research, 2022)